2008
DOI: 10.1016/s1567-4215(08)60383-5
|View full text |Cite
|
Sign up to set email alerts
|

Relation between aldosterone synthase polymorphism and atrial fibrillation in patients with systolic heart failure

Abstract: Background: Activation of the renin-angiotensin system (RAS) has been suggested to have an important role in the pathogenesis of atrial fibrillation (AF). Aldosterone synthase is a key enzyme in aldosterone production, the final product of the RAS. We analyzed the possible association between CYP11B2 T-344C polymorphism in aldosterone synthase, which is associated with increased aldosterone activity, and the prevalence of AF in patients with chronic systolic heart failure (HF). Methods: We studied 178 consecut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Although A1166C is not directly associated with stroke risk it correlates with stroke outcome in the aSAH group. Its effect on outcome was also shown in patients after percutaneous coronary interventions and in patients with heart failure and reduced systolic function patient [13,14]. Based on mice models several authors have shown that interaction of AII with activated T leukocytes contributes to T-cell cytokine production and tissue invasion [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although A1166C is not directly associated with stroke risk it correlates with stroke outcome in the aSAH group. Its effect on outcome was also shown in patients after percutaneous coronary interventions and in patients with heart failure and reduced systolic function patient [13,14]. Based on mice models several authors have shown that interaction of AII with activated T leukocytes contributes to T-cell cytokine production and tissue invasion [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…In patients after percutaneous coronary intervention it was associated with long term clinical outcome defined as death, repeat revascularization and myocardial infarction [13]. In heart failure and reduced systolic function it was associated with poor prognostic markers and increased mortality [14].…”
Section: Introductionmentioning
confidence: 99%